FAKTOR-FAKTOR PENYEBAB MISKONSEPSI SISWA SD PADA MATERI LIFE PROCESSES AND LIVING THINGS - Adi, Yogi Kuncoro; Oktaviani, Ndaru Mukti (Universitas Muhammadiyah Surakarta, 2019)
AbstractThe misconception is a common problem in the world of science learning. This study aims to reveal the types and causes of primary science misconception in the life processes and living things. Therefore, qualitative case studies were used in this study and the primary school students were subject to this study. The results showed that students who had misconceptions in the concept of living, classification, breathing, and microbe and disease. In addition, the causes of student misconceptions were the students' pre-concepts, humanist thinking, false reasoning, and associative thinking. Based on the findings of this study, it is recommended that learning must promote cognitive conflict to correct the student’s misconceptions.Keywords: misconception, primary science